Gut Microbiota: The Brain Peacekeeper - Mu, Chunlong; Yang, Yuxiang; Zhu, Weiyun (Frontiers in Microbiology, 2016)
Gut microbiota regulates intestinal and extraintestinal homeostasis. Accumulating evidence suggests that the gut microbiota may also regulate brain function and behavior. Results from animal models indicate that disturbances in the composition and functionality of some microbiota members are associated with neurophysiological disorders, strengthening the idea of a microbiota-gut-brain axis and the role of microbiota as a “peacekeeper” in the brain health. Here, we review recent discoveries on the role of the gut microbiota in central nervous system (CNS)-related diseases. We also discuss the emerging concept of the bidirectional regulation by the circadian rhythm and gut microbiota, and the potential role of the epigenetic regulation in neuronal cell function. Microbiome studies are also highlighted as crucial in the development of targeted therapies for neurodevelopmental disorders.